Assistance and Empowerment of Farmer Community in Past Eisesldp Project (A Case Study in Seven Districts in Southern Sulawesi, Gorontalo, and Northern Sulawesi Province) - A Saleh (Media Peternakan, 2003)
Assistance and empowerment of farmer community in past eisesldp project (A case study in seven districts in southern Sulawesi, Gorontalo, and Northern Sulawesi province)